Etika Digital dan Pancasila: Sinergi Transformasi Pelajar melalui Proyek Inovasi Teknologi Digital - Ricky Firmansyah; Saifuddin Hamzah; Almuntarizi Almuntarizi (Badan Pembinaan Ideologi Pancasila, 2025)
This study examines the integration of Pancasila values with digital ethics through the Project for Strengthening the Pancasila Student Profile (P5) based on information technology, aimed at shaping an ethical and responsible student character in the digital era. While digitalization offers numerous benefits, students are frequently exposed to challenges in digital ethics, such as the spread of hoaxes, cyberbullying, and plagiarism, due to a lack of understanding of digital ethics. Addressing this issue is crucial because without a solid understanding, technology can have a negative impact on students’ character and social interactions. This research employs a descriptive analysis method with a literature review approach to explore the concepts of digital ethics and Pancasila, as well as the challenges in implementing P5. The findings indicate that technology-based P5 allows students to apply Pancasila values, such as tolerance and justice, in their digital lives. However, challenges such as the digital access gap in remote areas and low digital literacy among educators need to be addressed. Therefore, collaboration among the government, educators, and society is essential to improve technology infrastructure, enhance digital literacy training, and create a supportive digital environment. With this approach, it is expected that P5 can produce a generation that is not only technologically adept but also virtuous.